AgrocIimatic zoning for sunflower in the State of Rio Grande do Sul, Brazil. - Mota, Fernando Silveira da (2014)
The recent literature on field experimentation in the state of Rio Grande do Sul, Brazil, with early sunflower cultivars sown in the beginning of spring, has shown the possibility for the obtention of economic yields in that state for the springtime. Considering those cultivars and this sowing time, most of the state area is climatically suitable for sunflower. Adopting the criteria of the sum of the degree-days above 50, higher than 1,400°C, and water deficiency in summer below 25 mm, three regions were identified; the largest one is the north-central part, with no climatic restrictions and considered perfect for that culture; the southern and litoral regions with a small water deficiency in summer but with economic yields, and the northeast highlands; and a small region, suitable only for very early cultivars due to a lack of heat for the maturation of other cultivars.